2003
DOI: 10.1039/b302183c
|View full text |Cite
|
Sign up to set email alerts
|

Secondary metabolites isolated from Colletotrichum species

Abstract: Structural and biosynthetic studies of the metabolites isolated from various Colletotrichum species are reviewed. These fungi are destructive post-harvest pathogens on a wide range of plants including cereals, legumes and fruits. The review includes a detailed study of the biological activity of these metabolites and their role in the development of plant diseases. The literature in this field to the present is reviewed and 60 references are cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 51 publications
2
70
0
Order By: Relevance
“…inhibited plant pathogens, e.g., Pyrenophora tritici-repentis on wheat [32] or powdery mildew on barley [66]. Similarly, various species of Colletotrichum are well-known sources of novel bioactive secondary metabolites [17,74]. An endophytic Colletotrichum sp.…”
Section: Discussionmentioning
confidence: 99%
“…inhibited plant pathogens, e.g., Pyrenophora tritici-repentis on wheat [32] or powdery mildew on barley [66]. Similarly, various species of Colletotrichum are well-known sources of novel bioactive secondary metabolites [17,74]. An endophytic Colletotrichum sp.…”
Section: Discussionmentioning
confidence: 99%
“…& Sacc. is a fungus that causes anthracnose disease or anthracnose fruit rod in some tropical fruit, which leads to both low yield and poor fruit quality from the time of harvest, during storage periods, and ultimately when marketed (Estrada et al 2000;García-Pajón and Collado 2003). The fungal pathogen attacks fruits in its early stage and remains during fruit growth (quiescent infection); however, the most severe damage is caused as the fruit ripens (Alvarez and Nishijima 1987).…”
Section: Introductionmentioning
confidence: 99%
“…According to reports by Garcia-Pajon and Collado [18], Amusa [19], and Liyanage et al [20], metabolites are employed in the breakdown of plant defences as evidenced by the death of tissues from which specific pathogens have been isolated. The major toxins isolated in the Study were identified as glycoproteins.…”
Section: Discussionmentioning
confidence: 99%